2020
DOI: 10.1073/pnas.1920013117
|View full text |Cite
|
Sign up to set email alerts
|

The alarmones (p)ppGpp directly regulate translation initiation during entry into quiescence

Abstract: Many bacteria exist in a state of metabolic quiescence where energy consumption must be minimized so as to maximize available resources over a potentially extended period of time. As protein synthesis is the most energy intensive metabolic process in a bacterial cell, it would be an appropriate target for down-regulation during the transition from growth to quiescence. We observe that whenBacillus subtilisexits rapid growth, a subpopulation of cells emerges with very low prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 71 publications
6
84
0
Order By: Relevance
“…Our findings are supported by a recent report showing that (p)ppGpp inhibits the activation of IF2 leading to the attenuation of initiation of translation during the switch from active growth to quiescence in the Gram-positive bacterium Bacillus subtilis (19).…”
Section: Resultssupporting
confidence: 90%
“…Our findings are supported by a recent report showing that (p)ppGpp inhibits the activation of IF2 leading to the attenuation of initiation of translation during the switch from active growth to quiescence in the Gram-positive bacterium Bacillus subtilis (19).…”
Section: Resultssupporting
confidence: 90%
“…Compared to the many targets discovered for (p)ppGpp in Gram-negative bacteria, little is known about (p)ppGpp targets in Gram-positive firmicutes. In many bacteria, GTPases can be competitively inhibited by (p)ppGpp, including the ribosomal translation factors EF-Tu, EF-G, RF3 and IF2 [ 28 , [36] , [37] , [38] , [39] ]. In S. aureus , (p)ppGpp was shown to inhibit two enzymes needed for GTP synthesis (HprT and Gmk) and five GTPases (RsgA, RbgA, Era, HflX and ObgE) that are implicated in ribosome assembly [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selective inhibition by ppGpp of the initiation functions of IF2, such as 30SIC formation and docking of the 50S subunit to yield a 70SIC, was confirmed in a recent study in which it was shown that inhibition of IF2 activity by ppGpp occurs also during cellular entry into quiescence ( Diez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 70%